THE EFFECT OF TRAINING AND HUMAN RESOURCES DEVELOPMENT ON EMPLOYEE PERFORMANCE IN THE SYAHBANDAR OFFICE OF TANJUNG PERAK SURABAYA THROUGH COMPETENCY - Dwi Ambar Anggraini; I Nyoman Sudapet; Hamzah Denny Subagyo (Journal of World Conference (JWC), 2019)
The purpose of this study is to find out the effect of training and development of human resources on employee performance through competence. This research is quantitative research. With a population of 143 employees. Data collection techniques using a questionnaire. The analysis technique used is Partial Least Square (PLS). The results of this study indicate that there is a significant influence between the Training variable (X1) on Competence (Y1) with the results of the hypothesis test p-value of 0.000 and t value of 4.091, there is a significant influence between the variables of Human Resource Development (X2) on Competence ( Y1) with the results of hypothesis testing p-value of 0.000 and t value of 11,494, there is a significant influence between Training variables (X1) on Employee Performance (Y2) with the results of hypothesis testing p-value 0,000 and t value of 5,273, influence significant between the variables of Human Resource Development (X2) on Employee Performance (Y2) with the results of hypothesis testing p-value of 0,000 and t value of 4,614 and there is a significant influence between Competency variables (Y1) on Employee Performance (Y2) with the results of hypothesis testing p-value of 0.034 and t value of 1.835.